Portrayal of professions in another life : a content analysis of the episodes run during the month of May, 1999 - Mbalangu, Vincent V. (Kampala : Makerere University, 1999)
Dissertation (B.A., Mass Comm.) - Makerere University, 1999
Includes bibliographical references (p. 54-56)
Keywords: Television broadcasting